Increased global interaction across functional brain modules during cognitive emotion regulation - Brandl, Felix; Bratec, Satja Mulej; Xie, Xiyao; Wohlschlager, Afra M.; Riedl, Valentin; Meng, Chun; Sorg, Christian (Cerebral Cortex, 2018)
Cognitive emotion regulation (CER) enables humans to flexibly modulate their emotions. While local theories of CER neurobiology suggest interactions between specialized local brain circuits underlying CER, e.g., in subparts of amygdala and medial prefrontal cortices (mPFC), global theories hypothesize global interaction increases among larger functional brain modules comprising local circuits. We tested the global CER hypothesis using graph-based whole-brain network analysis of functional MRI data during aversive emotional processing with and without CER. During CER, global between-module interaction across stable functional network modules increased. Global interaction increase was particularly driven by subregions of amygdala and cuneus—nodes of highest nodal participation—that overlapped with CER-specific local activations, and by mPFC and posterior cingulate as relevant connector hubs. Results provide evidence for the global nature of human CER, complementing functional specialization of embedded local brain circuits during successful CER.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Cognitive emotion regulation; Functional connectivity; Global interaction; Graph theory; Task fMRI